Electroencephalographic Changes in Pregnant Women with Hyperemesis Gravidarum: A Case–Control Study - Çelik, Meryem Nur; Aldemir, Ramazan; Sürmeli, Reyhan; Kale, İbrahim; Tokmakçı, Mahmut; Muhcu, Murat (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
Objective Electroencephalogram (EEG), which is frequently used in the clinical practice of neurology, has also been investigated in eating disorders and some cortical dysfunctions have been reported. Based on this, we aimed to investigate EEG changes in pregnant women with hyperemesis gravidarum (HEG).Materials and methods This case-control study was conducted on 66 pregnant women who applied to the Umraniye Training and Research Hospital, Department of Obstetrics and Gynecology. The study group consisted of 34 pregnant women diagnosed with HEG. The control group consisted of 32 healthy pregnant women who were matched with the HEG group in terms of age and gestational week. EEGs of the participants were performed with a Micromed Brain Rapid EEG device in the Neurology Department of Umraniye Training and Research Hospital. In EEGs, all channels were selected as bipolar and samples of 18 channels (Fp2-F4, F4-C4, C4-P4, P4-O2, Fp2-F8, F8-T4, T4-T6, T6-O2, Fz-Cz, Cz-Pz, Fp1-F3, F3-C3, C3-P3, P3-O1, Fp1-F7, F7-T3, T3-T5, and T5-O1) were obtained. EEG signals were sampled with a sampling frequency of 200 Hz and digitized with 12-bit resolution. EEG signals were converted to EDF (European Data Format) extension files using the MATLAB software program and analyzed using statistical features on the time and frequency axis. HEG and control groups were compared in terms of signals obtained from these 18 selected channels.Results Both groups were similar in terms of mean age, gestational age, and parity (p>0.05). Among the 18 channels, significant changes were detected between the two groups only in the theta, beta, and gamma bands in the C4-P4 channel and the delta, beta, and gamma bands in the T4-T6 channel (p<0.05). No significant changes were detected in the channels and bands.Conclusion Theta, beta, and gamma band abnormalities in the centro-parietal area of the right hemisphere and delta, beta, and gamma band abnormalities in the temporal area of the right hemisphere were observed on HEG. However, it is unclear whether abnormalities in EEG are primary changes responsible for the development of HEG or secondary to metabolic and hormonal changes resulting from HEG itself.
Keywords: Electroencephalogram; hyperemesis gravidarum; nausea; pregnancy; vomit